Dopaminergic mechanisms in the lateral hypothalamus regulate feeding behavior in association with neuropeptides - Naomi Yonemochi, - (Elsevier, 2019)
This study investigated dopaminergic function in the lateral hypothalamus (LH) in the regulation of feeding behavior. Refeeding increased dopamine levels in the LH. Glucose injection also increased dopamine levels in the LH. When the retrograde tracer Fluoro-Gold (FG) was injected into the LH, FG-positive cells were found in the ventral tegmental area (VTA) and the substantia nigra pars compacta (SNC), which were mostly tyrosine hydroxylase-positive. Injection of the dopamine D1 receptor agonist SKF 38393, but not the antagonist SCH 23390, into the LH increased food intake. Similarly, injection of the dopamine D2 receptor agonist quinpirole, but not the antagonist l-sulpiride, into the LH increased food intake. The effect of each agonist was blocked by its respective antagonist. Furthermore, injection of quinpirole, but not SKF 38393, decreased the mRNA level of preproorexin. In addition, injection of SKF 38393 decreased the mRNA levels of neuropeptide Y and agouti-related peptide, whereas the injection of quinpirole increased the mRNA level of proopiomelanocortin. These results indicate that food intake activates dopamine neurons projecting from the VTA/SNC to the LH through an increase in blood glucose levels, which terminates food intake by stimulation of dopamine D1 and D2 receptors. It is also possible that stimulation of dopamine D1 and D2 receptors in the LH inhibits feeding behavior through different neuropeptides.